Fulminating amoebic colitis with peritonitis: A diagnostic dilemma with high mortality - Sim L.K.; Muhaimin A.; Lee Y.L.; Arif N.A.M.; Adzman S.; Arief Hamid (Surgical Society of Northern Greece, 2024)
Indexed by SCOPUS